Paternal impact on the developmental programming of sexual dimorphism - Shefa’ M. Aljabali; Shefa’ M. Aljabali; Shruta Pai; Shruta Pai; Raffaele Teperino; Raffaele Teperino (Frontiers in Cell and Developmental Biology)
Sexual dimorphism involves distinct anatomical, physiological, behavioral, and developmental differences between males and females of the same species, influenced by factors prior to conception and during early development. These sex-specific traits contribute to varied phenotypes and individual disease risks within and across generations and understanding them is essential in mammalian studies. Hormones, sex chromosomes, and imprinted genes drive this dimorphism, with over half of quantitative traits in wildtype mice showing sex-based variation. This review focuses on the impact of paternal non-genetic factors on sexual dimorphism. We synthesize current research on how paternal health before conception affects offspring phenotypes in a sex-specific manner, examining mechanisms such as DNA methylation, paternally imprinted genes, sperm RNA, and seminal plasma. Additionally, we explore how paternal influences indirectly shape offspring through maternal behavior, uterine environment, and placental changes, affecting males and females differently. We propose mechanisms modulating sexual dimorphism during development, underscoring the need for sex-specific documentation in animal studies.